Application of Pyrazole Derivatives As New Substitutes of Auxin IAA To Regulate Morphometric and Biochemical Parameters of Wheat (Triticum Aestivum L.) Seedlings - Tsygankova, Victoria Anatolyivna; Ya.V, Andrusevich; O.I, Shtompel; V.M, Kopich; S.Ya, Panchyshyn; R.M, Vydzhak; V.S, Brovarets (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
The regulating activity of new synthetic low molecular weight heterocyclic compounds, pyrazole derivatives on morphometric, and biochemical parameters of wheat (Triticum aestivum L.) seedlings was studied. The synthetic compounds used at the concentration 10-8M revealed auxin-like stimulating effect on morphometric parameters of 6th-week-old wheat seedlings, which were increased on average: to 31 - 54 % – for total number of roots, to 39 – 104 % – for full length of sources, to 53 - 66 % – for length of the longest root as compared with similar parameters of the wheat seedlings grown in the distilled water (control) or water solution of auxin IAA (1H-Indol-3-ylacetic acid). The synthetic compounds used at the concentration 10-8M revealed cytokinin-like stimulating effect on biochemical parameters of 6th-week-old wheat seedlings. The content of photosynthetic pigments in the leaves of the wheat seedlings grown in the water solution of the pyrazole derivatives used at the concentration 10-8M increased on average: to 15-34 % – for content of chlorophyll a, to 10-61 % – for content of chlorophyll b, to 16–34 % – for content of chlorophylls a+b, to 14–28 % – for content of carotenoids, as compared with similar indices of the wheat seedlings grown in the distilled water (control) or water solution of auxin IAA. The practical application of pyrazole derivatives to regulate morphometric and biochemical parameters of wheat seedlings was proposed.